Strategic Engineering for Cloud Computing and Big Data Analytics - Hosseinian-Far, Amin.; Ramachandran, Muthu; Sarwar, Dilshad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book demonstrates the use of a wide range of strategic engineering concepts, theories and applied case studies to improve the safety, security and sustainability of complex and large-scale engineering and computer systems. It first details the concepts of system design, life cycle, impact assessment and security to show how these ideas can be brought to bear on the modeling, analysis and design of information systems with a focused view on cloud-computing systems and big data analytics. This informative book is a valuable resource for graduate students, researchers and industry-based practitioners working in engineering, information and business systems as well as strategy. .
Part I: Systems Lifecycle, Sustainability, Complexity, Safety and Security -- Through-Life Systems Sustainment in Computing -- System of Systems and Complexity -- Systems Lifecycle and Impact Assessment -- Theoretical Concepts and Models -- Systems Safety and Security -- Part II: Systemic Modelling, Analysis and Design for Cloud Computing and Big Data Analytics -- Approaches to Modelling and Methodologies -- Applied Systems Analysis and Design -- Systems Architecture and Processes -- Decision Engineering -- Part III: Cloud Services, Big Data Analytics and Business Process Modelling -- Strategic Approaches to the Federation of Cloud Services -- Business Process Modelling, Patterns and Transitions -- Strategic Approaches to Big Data -- Strategic Analytics and Visualisation.
Keywords: Security systems; Computer networks .; Business information services; Electronic data processing -- Management; Quantitative research; Telecommunication; Security Science and Technology; Computer Communication Networks; Business Information Systems; IT Operations; Data Analysis and Big Data; Communications Engineering, Networks